2013
DOI: 10.2176/nmc.53.561
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Disease in Pregnancy: A Single Institute Experience

Abstract: Moyamoya disease is a rare chronic, occlusive cerebrovascular disease characterized by bilateral stenoocclusive changes at the terminal portion of the internal carotid artery and an abnormal vascular network at the base of the brain. Moyamoya disease particularly affects children and young adults with female predominance, thus pregnant patients with moyamoya disease are not uncommon. Among 4,400 patients with consecutive deliveries in our hospital, 6 patients (0.14%) aged from 24 to 40 years (mean 32.7 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Physiologic changes associated with pregnancy include increased blood volume and hypercoagulation resulting in vasospasm that may cause consequential neurologic sequelae in patients with MMD [6]. Though a limited number of studies report the incidence of cerebrovascular accidents associated with MMD in pregnancy, there are reported cases from Japan and Korea that indicate that the rate of CVE's is higher, with a much poorer prognosis, in those lacking appropriate care, especially if diagnosed in pregnancy when compared with patients who have pre-existing MMD prior to gestation [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologic changes associated with pregnancy include increased blood volume and hypercoagulation resulting in vasospasm that may cause consequential neurologic sequelae in patients with MMD [6]. Though a limited number of studies report the incidence of cerebrovascular accidents associated with MMD in pregnancy, there are reported cases from Japan and Korea that indicate that the rate of CVE's is higher, with a much poorer prognosis, in those lacking appropriate care, especially if diagnosed in pregnancy when compared with patients who have pre-existing MMD prior to gestation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Though a limited number of studies report the incidence of cerebrovascular accidents associated with MMD in pregnancy, there are reported cases from Japan and Korea that indicate that the rate of CVE's is higher, with a much poorer prognosis, in those lacking appropriate care, especially if diagnosed in pregnancy when compared with patients who have pre-existing MMD prior to gestation [6,7]. Prognosis is reportedly much improved when blood pressures are tightly controlled.…”
Section: Discussionmentioning
confidence: 99%
“…As the circulating blood volume increases and blood coagulation intensifies, pregnancy-induced hypertension occurs, causing blood-brain barrier disruption and vasospasm, which in turn induces neurological deterioration in pregnant women with MDD. 11 Therefore, it is thought that preventing cerebral ischemia and cerebral hemorrhage during pregnancy is important in patients with MMD. Although only a few studies have reported the pregnancy outcomes associated with MMD, recent results indicate that pregnant women diagnosed with MMD before pregnancy exhibit a lower incidence of cerebrovascular events than those diagnosed with MMD during pregnancy and puerperium.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section has previously been chosen as the mode of delivery in 69.7-100% of such cases. [5][6][7] Typically, vaginal delivery is avoided to reduce the risk of cerebral ischemia due to hyperventilation and intracranial hemorrhage caused by increased blood pressure. 5 Cesarean section was required for specific indications in seven of the 27 pregnancies (26%) in our study, but overall our findings suggest that in patients with Moyamoya disease, it is quite possible to avoid unnecessary cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…In a nationwide survey of pregnancy with Moyamoya disease in Japan, Takahashi et al 5 found a cesarean section rate of 69.7-76.3%. Fujimura et al described six cases of pregnancy with Moyamoya disease, all of which underwent cesarean section, 6 and Fukushima et al reported the selection of cesarean section in 18 of 22 (82%) pregnancies with Moyamoya disease. 7 Cesarean section is generally chosen over vaginal delivery to avoid cerebral ischemia due to hyperventilation and intracranial hemorrhage caused by increased blood pressure.…”
Section: Introductionmentioning
confidence: 99%